A case report of advanced small intestinal stromal tumor with KIT gene mutation and BRCA2 deletion after multi-line treatments - Cui, Shiyun; Fan, Lei; Bai, Yu; Sun, Xinnan; Cai, Yucheng; Dai, Jingqi; Wang, Ting; Sun, Chongqi; Wang, Rong; Liu, Lianke (Frontiers in Oncology, 2025)
This study reports a 40-year-old male with small intestinal stromal tumor (SIST). After initial surgery and adjuvant imatinib, the tumor recurred. The patient then received multiple rounds of treatment with targeted drugs and surgical interventions. Through comprehensive analysis of gene mutation profiles (KIT and HRR gene mutations, including BRCA2), a combination therapy of fluzoparib, pamiparib, and ripretinib was administered, stabilizing the patient’s condition with significant efficacy. This case highlights the importance of genetic testing and personalized targeted treatment strategies for gastrointestinal stromal tumor (GIST) patients.